The Application of Green Materials and Practice of Environmental Protection Concepts in Architectural Interior Design - Yang, Yimeng (Transactions on Economics, Business and Management Research, 2024)
This article explores the widespread application of green materials in architectural interior design and their importance for environmental protection and sustainable development. Firstly, the paper provides an overview of the definition and development process of green materials, with a focus on common green materials and their characteristics. Secondly, the paper explores the advantages of green materials in improving indoor space comfort and health, as well as their applications in interior decoration and furniture. Subsequently, the paper analyzed the challenges faced in promoting green materials in interior design, including cost, technology, market recognition, and proposed corresponding solutions. Finally, the paper summarizes the development trend of green materials in interior design of buildings in the future, and points out the importance of joint efforts by the government, enterprises, and various sectors of society to promote the widespread application of green materials and achieve the goals of green buildings and sustainable development.